Content specificity of attentional bias to threat in post-traumatic stress disorder. (August 2017) - Zinchenko, A.; Al-Amin, M.M.; Alam, M.M.; Mahmud, W.; Kabir, N.; Reza, H.M.; Burne, T.H.J.
Highlights: We studied the content specificity of attentional bias to threat in PTSD patients. PTSD participants showed a stimulus specific dissociation in processing emotional stimuli. PTSD patients showed an involuntary content-sensitive attentional bias to emotional information. Abstract: Background: Attentional bias to affective information and reduced cognitive control may maintain the symptoms of post-traumatic stress disorder (PTSD) and impair cognitive functioning. However, the role of content specificity of affective stimuli (e.g., trauma-related, emotional trauma-unrelated) in the observed attentional bias and cognitive control is less clear, as this has not been tested simultaneously before. Therefore, we examined the content specificity of attentional bias to threat in PTSD. Methods: PTSD participants (survivors of a multistory factory collapse, n  = 30) and matched controls ( n  = 30) performed an Eriksen Flanker task. They identified the direction of a centrally presented target arrow, which was flanked by several task-irrelevant distractor arrows pointed to the same (congruent) or opposite direction (incongruent). Additionally, participants were presented with a picture of a face (neutral, emotional) or building (neutral = normal, emotional = collapsed multistory factory) as a task-irrelevant background image. Results: We found that PTSD participants produced overall larger conflict effects and longer reaction times (RT) to emotional than to neutral stimuli relative to their healthy counterparts. Moreover, PTSD, but not healthy participants showed a stimulus specific dissociation in processing emotional stimuli. Emotional faces elicited longer RTs compared to neutral faces, while emotional buildings elicited faster responses, compared to neutral buildings . Conclusions: PTSD patients show a content-sensitive attentional bias to emotional information and impaired cognitive control.